CONTENT ANALYSIS ON THE ROLE OF @BUMIJO.ID SOCIAL MEDIA IN RAISING CONSUMER AWARENESS OF ENVIRONMENTAL ISSUES - Annisa Anindya; Syaza Yasmin; Novi Elian; Fayrusatul Qolbi; Silis; Yayuk Lestari (Jurnal Ranah Komunikasi, 2026)
The social media account @bumijo.id focuses on education and promoting an environmentally friendly lifestyle. The @Bumijo social media platform has the potential to serve as a campaign medium for environmental awareness. This research aims to analyze the Instagram content of @bumijo.id in building environmental awareness among social media consumers. The content analysis is viewed from the perspective of the social media audience. The study uses a quantitative approach to determine the influence of attitudes, subjective norms, and perceived behavioral control on the intention to purchase environmentally friendly products offered by Bumijo. Furthermore, a qualitative approach is used to understand the forms of environmentally friendly behavior, the utilization of social media, and the barriers to implementing eco-living. Quantitative data were collected using a questionnaire and analyzed using multiple regression, while qualitative data were obtained through focus group discussions and interviews and analyzed using the data analysis model of reduction, presentation, and conclusion drawing. Attitudes, subjective norms, and perceived control simultaneously influence the intention to purchase eco-friendly products by 22.5%. Literacy regarding eco-living is considered low, with implementation barriers predominantly due to the high cost of products.